2016
DOI: 10.1186/s13034-016-0118-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a classroom-based intervention on the social skills of pupils with intellectual disability in Southwest Nigeria

Abstract: Background: Studies have demonstrated that social skill interventions and classroom supports are effective for pupils with intellectual disability. Such interventions have been demonstrated to reduce the risk of developing mental disorders, majority of which have their onset during the period of youth. Most young people with intellectual disability in low-resource settings do not have access to interventions that would enable or enhance their participation in society. The aim of this study was to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 67 publications
(97 reference statements)
3
30
1
2
Order By: Relevance
“…According to the findings, this assumption was not approved. This finding was not consistent with the previous studies [24][25][26]. For explaining this finding, it can be said that improving social skills through some training sessions is partly impossible; also, the non-significant effects of cognitive rehabilitation on the social skills does not mean that such intervention is not useful rather it implies that targeting the underlying mechanism of social skills (adaptive behavior and executive functions) should be addressed early and for long period, as well as in a continuous way, since this population show the improvement of social skills in different settings.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…According to the findings, this assumption was not approved. This finding was not consistent with the previous studies [24][25][26]. For explaining this finding, it can be said that improving social skills through some training sessions is partly impossible; also, the non-significant effects of cognitive rehabilitation on the social skills does not mean that such intervention is not useful rather it implies that targeting the underlying mechanism of social skills (adaptive behavior and executive functions) should be addressed early and for long period, as well as in a continuous way, since this population show the improvement of social skills in different settings.…”
Section: Discussioncontrasting
confidence: 99%
“…When children with poor executive functions experience problems in social interaction, they are separated from peers and may experience other difficulties in a particular situation [23]. Previous studies investigated the social skills training of this population and reported positive consequences [24][25][26]. So, there is a necessity to understand the best intervention to improve executive functions and the social skills of this population to improve their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained findings indicating the absence of significant age differences in self-efficacy are supported by the results of previous studies (Gresham et al, 1988;Payne & Jahoda, 2004). Similarly, the results which refer to sense of relatedness are consistent with the findings of other authors according to which, in persons with ID, there were no significant age differences in social skills (Adeniyi & Omigbodun, 2016;Heiman & Margalit, 1998), peer acceptance and relations (Heiman & Margalit, 1998;Wendelborg & Kvello, 2010), and perceived social support (Lunsky & Benson, 2001). In interpreting these findings, Nota and colleagues (2007) made a significant observation that the limited experiences and opportunities that hinder individual qualities of people with ID override any age-related effects.…”
Section: Discussionsupporting
confidence: 82%
“…Nota and associates (2010) explained the lack of differences in self-efficacy beliefs in male and female persons with ID by the fact that school and extra scholastic activities for individuals with ID were rarely differentiated by gender, and thus girls and boys with ID mainly had similar experiences. The results of this research which refer to individual qualities in the sense of relatedness domain, are consistent with the findings of other authors indicating that in children and adolescents with ID gender was not significantly related to peer acceptance and relations (Smoot, 2004;Wendelborg & Kvello, 2010) or social skills (Adeniyi & Omigbodun, 2016;Heiman & Margalit, 1998). This is further supported by empirical findings that academic competence, physical appearance and behavior problems had more influence on the status of persons with ID in their peer group than gender (Baydik & Bakkaloğlu, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…Studies have shown that social skills interventions and classroom supports are effective for students with MID, as such interventions have been veri ed to reduce the risk of developing mental disorders. The strategies for teaching social skills such as modeling, role playing, positive reinforcement, practice/rehearsal, incidental teaching, prompting, and coaching would help the adolescents begin and extend positive social relationships with others [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%